Ratio-based Resuscitation in Trauma Patients with Traumatic Brain Injury: Is There a Similar Effect?. Issue 3 (March 2016) - Jokar, Tahereh Orouji; Khalil, Mazhar; Rhee, Peter; Kulvatunyou, Narong; Pandit, Viraj; O'Keeffe, Terence; Tang, Andrew; Joseph, Bellal
The use of 1:1:1 (packed red blood cells: fresh frozen plasma: platelets) transfusion ratio has been shown to improve survival in severely injured trauma patients. The aim of this study was to assess the outcomes in patients with traumatic brain injury (TBI) receiving 1:1:1 ratio-based blood product transfusion (RBT). We hypothesized that RBT improves survival in patients with TBI as only major injury. We performed a 3-year retrospective analysis of all patients with TBI as only major injury presenting to our Level I trauma center. Patients receiving blood transfusion were included. Patients were stratified into two groups: those who received RBT and those who did not receive RBT (No-RBT). The outcome measure was inhospital mortality. Multivariate logistic regression analysis was performed. A total of 189 patients were included of which 29 per cent (n = 55) received RBT. The mean age was 48 ± 24 years, median (range) Glasgow Coma Scale score was 12 (3–15), and median head abbreviated injury severity scale was 3 (3–5). The overall mortality rate was 28.5 per cent. Patients in the RBT group had a higher survival rate compared with the patients in the No-RBT group (83.6% vs 66.5%, P = 0.02). In conclusion, the survival benefit of RBT exists even in patients with TBI as major injury. Guidelines for the initial management of TBI patients should focus on the use of RBT. The beneficial effect of platelets in RBT among TBI patients requires further evaluation.